Analisis Unit Cost Quality Control Kimia Klinik dengan Metode Activity Based Costing di Laboratorium Rumah Sakit Paru dr. H. A. Rotinsulu - Suryadi, Arfiah Azzahra Nissa; Kurniawan, Entuy; Rahayu, Ira Gustira; Rinaldi, Sonny Feisal; Hidayatullah, Taufik (Journal of Indonesian Medical Laboratory and Science, 2025)
Hospital laboratories must comply with quality and safety standards as they are responsible for patients' health test results. Laboratory test results must be reliable, so the quality of laboratory services needs to be improved, including implementing quality control measures. Conducting a unit cost analysis for quality control activities is necessary to determine the expenses incurred for each quality control activity. The objective of this writing is to determine the unit cost for Clinical Chemistry Quality Control in the laboratory using the Activity-Based Costing method. Data collection techniques include interviews, observations, and document studies. Various costs are involved in determining the ABC method, including labor costs, depreciation costs for equipment or buildings, and other costs. In addition to cost data, cost drivers are also important in determining them. The equipment used in this research is the Sysmex BX with a total of 14 examination parameters, including glucose, total bilirubin, direct bilirubin, SGOT / AST, SGPT / ALT, total protein, albumin, urea, creatinine, uric acid, cholesterol, triglycerides, HDL, LDL. Based on the research results, the cost of QC for clinical chemistry examinations is Rp. 102,477